Immunological Mechanism of the Low-Dose Radiation-Induced Suppression of Cancer Metastases in a Mouse Model - Ewa M. Nowosielska; Aneta Cheda; Jolanta Wrembel-Wargocka; Marek K. Janiak (SAGE Publishing, 2010)
According to the doctrine underlying the current radiation protection regulations each, no matter how small, exposure to ionizing radiation may be carcinogenic. However, numerous epidemiological observations demonstrate that cancer incidence and/or mortality are not elevated among inhabitants of the high- versus low-natural-background radiation areas and homes. Results of our own and other authors' studies described in this paper bear testimony to the possibility that stimulation of the anti-neoplastic immune surveillance mediated by NK lymphocytes and activated macrophages explains, at least partially, the accumulating epidemiological and experimental evidence indicating that low-level exposures to the low-linear energy transfer (LET) radiation inhibit the development of spontaneous and artificial metastases in humans and laboratory animals, respectively. The results presented also suggest the possibility of using low-level X- and gamma-ray exposures to cure cancer and to prevent cancer metastases. For a broader perspective, the results presented may help towards relaxing the current radiation protection regulations, especially as they apply to diagnostic and therapeutic exposures of patients to the indicated forms of radiation.